House Prices in Norway 1819-1989 - Øyvind Eitrheim; Solveig K. Erlandsen (Norges Bank, 2004)
Annual house price indices for four Norwegian cities are presented for the period from 1819 to 1989. The indices are constructed on the basis of nominal housing transaction prices compiled from the real property registers of the cities. Existing Norwegian house prices indices generally cover a few decades and usually start in the mid-1980s. Hence, we present new information about Norwegian house prices for more than 160 years. The house price indices seem to fit well in with historical events and available indicators of the Norwegian economy. The overall trend in nominal house prices is upward sloping over the two centuries. However, in real terms the picture looks different, in particular in the first half of the twentieth century.
hdl:11250/2498531
Keywords: N10; E31; C81; 330; economic history; house prices; repeat sales indices